TINGKAT PARASITEMIA MENCIT PUTIH (Mus musculus L.) JANTAN GALUR DDY DIINFEKSI Trypanosoma evansi ISOLAT PIDIE DAN PEMALANG (Parasitemia Level of Male White Mice (Mus musculus L.) DDY Strain Infected with Trypanosoma evansi of Pidie and Pemalang Isolate) - Febiola Rama Sari; Yudha Fahrimal; Ummu Balqis; Aprilia Wardana; Muhammad Hambal (Universitas Syiah Kuala, 2015)
This study aimed to observe parasitemia of DDY white mice infected with T. evansi of Pidie and Pemalang isolates obtained from Balai Besar Penelitian Veteriner (BBPV) Bogor. Twelve DDY mice were divided into 3 groups, each group consisted of 4 mice. Mice in the first group were not treated with any treatment. The second group was inoculated with 104 T. evansi Pidie isolate and the third group was inoculated with 104 T. evansi of Pemalang isolate. Mice blood were collected every two days from tail vein for parasitemia examination. Parasitemia examination was conducted until all mice die. The results indicate that there was difference in parasitemia level between the two isolates. Parasitemia of mice infected with Pidie isolate characterized by rapid rise of parasitemia in blood (107-108/mL of blood) in a short time (2-4 days) since first parasitemia was detected and followed by death at day 4. While the parasitemia of mice infected with Pemalang isolate increased in the blood (108-109/mL of blood) on day 4 and maintained for a few more days and then fluctuated for a few more days before the animal died.Key words: Trypanosoma evansi, parasitemia, Pidie isolate, Pemalang isolate